2014
DOI: 10.1016/j.jde.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

On the behavior of the solution of the dissipative Camassa–Holm equation with the arbitrary dispersion coefficient

Abstract: In this paper, we consider the dissipative Camassa-Holm equation with arbitrary dispersion coefficient and compactly supported initial data. We demonstrate the simple conditions on the initial data that lead to finite time blow-up of the solution in finite time or guarantee that the solution exists globally. Also, propagation speed for the equation under consideration is investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
(42 reference statements)
2
9
0
Order By: Relevance
“…In particular, the propagation speed is seriously affected by both the dissipative parameter λ and the dispersion coefficient k. On the other hand, it is worthy to note that the main difficulty in establishing the above results lies in controlling certain norms of (N +1)-order nonlinearities. In addition, some of our results cover the earlier corresponding results studied in [29,37].…”
Section: Introductionsupporting
confidence: 87%
“…In particular, the propagation speed is seriously affected by both the dissipative parameter λ and the dispersion coefficient k. On the other hand, it is worthy to note that the main difficulty in establishing the above results lies in controlling certain norms of (N +1)-order nonlinearities. In addition, some of our results cover the earlier corresponding results studied in [29,37].…”
Section: Introductionsupporting
confidence: 87%
“…Recently, Novruzov [1] studied the Cauchy problem for the weakly dissipative Dullin-Gottwald-Holm (DGH) equation (i.e (1.1) with N = , c = , b = , a = ) and establish certain conditions on the initial datum to guarantee that the corresponding positive strong solutions blow up in nite time. The same equation for arbitrary solution has been considered in [44]. Authors showed the simple conditions on the initial data that lead to the blow-up of the solutions in nite time or guarantee that the solutions exist globally.…”
Section: Introductionmentioning
confidence: 99%
“…It is found [13,15,20]that such kinds of considerable differnces were investigated for the different model (nonlinear wave equations). Recently, Novruzov and Hagverdiyev [17] analyzed the behavior of solutions to the dissipative Camassa-Holm equation with arbitrary dispersion coefficient. In the present paper, we discuss the global existence and the propagation speed of strong solutions to the equation (1).…”
Section: Introductionmentioning
confidence: 99%